2003
DOI: 10.1002/jsfa.1403
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating quality of yellow alkaline noodles made from mechanically abraded sprouted wheat

Abstract: Five hard red spring wheat genotypes, with initial falling numbers (FNs) ranging from 62 to 427 s, were mechanically abraded for 30, 60, and 120 s to reduce sequentially α-amylase activity in the grain. Mechanical abrasion prior to milling significantly increased FN and reduced amylase activity in preharvest sprouted wheat. The abraded grains were milled and the resultant flour samples were evaluated for starch gelatinization properties and yellow alkaline noodle (YAN) quality. Mechanical abrasion on sprouted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 15 publications
1
24
0
Order By: Relevance
“…Sprouting buckwheat grains have little market value (Bluett, 2001), because some buckwheat millers and manufacturers speculate that fl our made from sprouting grains leads to fragile noodles. Preharvest sprouting occurs in other cereals such as wheat, and seriously degrades grain quality (Kruger, 1990;Noda et al, 2001;Ichinose et al, 2002;Chakraborty et al, 2003).…”
mentioning
confidence: 99%
“…Sprouting buckwheat grains have little market value (Bluett, 2001), because some buckwheat millers and manufacturers speculate that fl our made from sprouting grains leads to fragile noodles. Preharvest sprouting occurs in other cereals such as wheat, and seriously degrades grain quality (Kruger, 1990;Noda et al, 2001;Ichinose et al, 2002;Chakraborty et al, 2003).…”
mentioning
confidence: 99%
“…Serious cooking loss is undesirable because it means that there was a high starch content in the cooking medium and that the noodles had a low cooking tolerance (Chakraborty et al, 2003). As shown in Table 2, the cooking loss of acidified noodles in this study showed a significant increase (P<0.05) when the concentration of the acid used for the noodle treatment increased.…”
Section: Resultsmentioning
confidence: 60%
“…The texture of cooked noodles is considered the most critical characteristic in evaluating the quality of noodles and determining consumer acceptance of the product (Bhattacharya et al, 1999). Tensile strength represents the consumption quality of noodles, and it also corresponds to elasticity of the noodles (Chakraborty et al, 2003). The Japanese preference for woo-long noodle is for a softer, slightly more elastic and adhesive texture.…”
Section: Resultsmentioning
confidence: 99%
“…1 The general process flow of dough wrapper is introduced at first in this article. The main processes are, (1) press dough wrapper to the thickness of 6 mm by continuous pressing machine, (2) transfer dough wrapper to the fixed-length cutting device by the dough wrapper conveyer, (3) cut off dough wrapper with a fixed-length under the control of the photoelectric sensor, (4) roll up cut -off dough wrapper to roller die by the dough wrapper rolling device while transferring roller die of the storage device to the dough wrapper rolling device by chain transmission at a fixed frequency, and (5) sent dough wrapper to fermenting box through the chain.…”
Section: Architectural Designmentioning
confidence: 99%
“…Japanese Nissin Food Products Co., Ltd. has developed automatic production lines of the fresh wet noodles ,in which the fixed-length cutting and rolling device has played a very important role. There is currently no manufacturer that could develop automatic device of the wrapper fixed-length cutting and rolling for alkaline noodle in the domestic market [1][2][3][4] . Common components, such as water purification equipment, mixing equipment, rolling and slitting, packaging equipment, have been relatively mature in production of fresh wet noodle [5,6] .But the components like wrapper cutting and rolling device are still relatively simple and backward, mainly by performing simple reforms of the original dry noodle production equipment to produce fresh wet noodle.…”
Section: Introductionmentioning
confidence: 99%